PENYELESAIAN MASALAH KONTROL KUADRATIK LINIER YANG MEMUAT FAKTOR DISKON - Mezi Fauziatul Husna (Jurusan Matematika FMIPA Universitas Andalas Padang, 2013)
The linear quadratic control problem is an optimal control problem whichhas been used in various fields. In this paper, we will study the solving of linear quadraticcontrol problem that contains a discount factor. By using the change of variables technique, some sufficient condition for the existence of optimal control is determined. Someexamples are also presented.